What Imply Modern Kids’ Reading Habits and Games - Katerina Polivanova; Elena Sazonova; Marta Shakarova (Voprosy obrazovaniya / Educational Studies Moscow, 2014)
Katerina Polivanova - Professor, Institute for Educational Studies, National Research University Higher School of Economics. Address: 20 Myasnitskaya str., Moscow, 101000, Russian Federation. E-mail: kpolivanova@mail.ruElena Sazonova - Postgraduate student, Psychological Institute of Russian educational academy. Address: 9 Mokhovaya str., Moscow, 119019, Russian Federation. E-mail: sazonova_ev@mail.ruMarta Shakarova - Ph.D, Researcher at Recruiting Company «Beagle». Address: 19 Leninskaya sloboda str., Moscow, 115280, Russian Federation. E-mail: roxish@mail.ruThe authors interpret the fact that modern kids’ maturation conditions change as compared to conditions in which their parents grew up as deepening of «the childhood crisis». Modern kids’ maturation is mediated to a much lesser extent by clear and well-defined development prospects, by close relations with adults. And by the authors’ hypothesis, cultural texts start act as child development mediators. In this regard an issue concerning a developmental potential of these texts is raised. The authors give reasons for necessity of new developmental psychology research in the context of a culture-historical theory that would be based on updated data. Two empirical studies are described. An analysis of a preschoolers’ game inspired by plots of modern animated series revealed, in the first place, a possibility in principle to organize games with the developmental potential on the basis of modern animated cartoons, and in the second place, a kids’ ability to use for their games plots where relations between characters are complicated and mixed. These data expand the notion of a child’s play prototype, and so far it was considered to be a fairytale with well-defined boundaries of good and evil. Modern kids can reproduce while playing more sophisticated and more complicated relations between characters. To find out why books about Harry Potter written by J. Rowling are so popular with adolescents, pupils of the 8th-10th grades were interviewed, as well as participants of Internet forums on Potteriana. Respondents also took some projective tests. It turns out that for adolescents an initiative action, an outstanding, heroic deed with an unknown result has a great appeal. Besides, the adolescents attribute a possibility of such an action to a fantasy, magic world, аnd as for the physical reality, they qualify it as gray and dull. On the basis of these findings the authors draw a conclusion that modern cultural texts imply a sophisticated spectator and reader, give freedom and openness, offer to take action in a situation of ambiguity and uncertainty; that is to say, they form a non-didactic mode of interaction in principle. Modern cultural texts for kids and adolescents have the developmental potential but are ignored by an educational system.